PHYTOMONITORING OF BRICK KILN INDUCED AIR POLLUTION AT KONABARI OF BANGLADESH - Roy Tusher, Tanmoy; Akter, Shilpi; Ashraf, Zisan; Kabir, Md. Humayun; Siddiqui, Md. Nurealam (Malaysian Journal of Science, 2018)
The study was conducted to assess the effects of brick kiln induced air pollution on the surrounding vegetation as a function of distance at Baghiya of Konabari union in Gazipur district of Bangladesh. Four samples of two indigenous (Mangifera indica and Artocarpus heterophyllus) and two exotic (Eucalyptus camaldulensis and Acacia auriculacformis) plant species, mostly common in the study area, were collected from three sampling stations (southwest of brick kilns following the prevailing wind) which were 200m away from each other to analyze total chlorophyll, Na+, K+, K+/Na+ ratio, total sugar and proline contents. The study observed that a reduction in total chlorophyll, Na+ and total sugar contents in the leaf samples of all sampled plant species at SS-1 (near source station) when compared to the samples at SS-3 (distant station). The study found that indigenous plant species were more sensitive in case of the total chlorophyll content, whereas exotic plant species were more sensitive in case of total sugar content. At SS-1, the lower value of K+ content and higher value of K+/Na+ ratio were found in all plant species than at SS-3 except E. camaldulensis and A. auriculacformis, respectively. The lower level of proline content was observed in M. indica (240.00 µg/g) and A. heterophyllus (249.05 µg/g) at SS-1, whereas the higher level of proline content was found in E. camaldulensis (388.00 µg/g) and A. auriculacformis (354.09 µg/g) at SS-1 when compared to SS-3 which indicated that the more sensitivity of indigenous plant species to air pollution than exotic plant species. Monitoring of existing kilns and strictly following of brick kiln related rules and regulations in installing new kilns is, thus, necessary for minimizing the impacts of air pollution in the study area. Keywords: Phytomonitoring, brick kiln, air pollution, indigenous and exotic species.